PERBEDAAN PENYESUAIAN DIRI ANTARA MAHASISWA YANG AKTIF BERORGANISASI DENGAN YANG TIDAK AKTIF BERORGANISASI PADA UNIVERSITAS BUNDA MULIA - Eka Kurnia; Maria Dwi Yanika Hesti Nugraha (Psibernetika, 2012)
Adjustment can be defined as an individual's ability to identify with group expectations. A healthy individual should be able to understand the expectations of the individual place in accordance with these expectations. Students have to make adjustments to the new situations and demands, such as self-study without having to be supervised, be prepared for sudden in-class exams, studying in groups. Disability in adjustment to the demands of the existing situation. This research is a comparative study. The subject was the entire board and members of student organizations and who are not members of student organizations at the University of Bunda Mulia. Collecting data using a questionnaire modified from the questionnaire Bell Adjustment Inventory (1934). Test the validity of the instruments is done by using a test construct validity, the reliability values to 0915. Analysis of research data used non-parametric Mann Whitney test with the result that there was no difference in the correlation between students who are in organization and not in organization. Keyword: self adjusment, student, organizational